Development and validation of the stability-indicating LCâUV method for the determination of Cefditoren pivoxil - M. Mathrusri Annapurna; S.V.S. Goutam; S. Anusha; L. Srinivas (Elsevier, 2012)
An isocratic RP-HPLC method was developed for the determination of Cefditoren pivoxil in pharmaceutical formulations using a C-18 column with waterâacetonitrile (50:50, v/v) as mobile phase and flow rate 1.2Â mL/min (UV detection at 218Â nm). Linearity was observed in the concentration range 1.0â250Â Î¼g/mL (R2=0.999) with regression equation y=24194x+10749. The forced degradation studies were performed by using HCl, NaOH, and H2O2, and thermal and UV radiation. Cefditoren pivoxil is more sensitive towards oxidation and alkaline conditions and resistant towards acidic and photolytic degradations. The method was validated as per ICH guidelines. Keywords: Cefditoren pivoxil, Liquid chromatography, Stability-indicating, Validation